Simulated patient scenario development: A methodological review of validity and reliability reporting. (February 2020) - Mirza, Noeman; Cinel, Julie; Noyes, Heather; McKenzie, Wendy; Burgess, Kim; Blackstock, Sheila; Sanderson, Darlene
Abstract: Introduction: Some healthcare scholars (educators and researchers) develop their own simulated patient scenarios to address specific learning objectives. Clear processes of validity and reliability are needed in the development of simulated scenarios for the purpose of replication and the transfer of findings to other contexts. Methods: This paper reports a methodological review of CINAHL to determine how valid and reliable simulated patient scenarios are developed. We reviewed 375 abstracts based on specific inclusion and exclusion criteria to yield 17 qualifying records. Data about the discipline, population, type of simulation, and validity and reliability processes were extracted. Results: Selected records were from nursing, medicine, and paramedicine. While some studies used high-fidelity simulations, some used low-fidelity or a combination of high- and low-fidelity simulations. Scholars validated scenarios by using personal experience, consulting experts, or requesting participant feedback. They also examined different types of validity (face, content, construct). Most studies did not address how reliability of scenarios was determined. To ensure consistency in scenario delivery, some studies piloted scenarios with participants, or examined performance through video-tapes or virtual patients. Conclusions: This review shows that scholars use inconsistent processes to develop valid and reliable simulated patient scenarios, often overlooking evidence-based approaches to determining validity and reliability. Future practices pertaining to scenario development should use systematic processes in determining validity and reliability so simulation exercises can be replicated in other contexts.